(untitled) (Swiss Medical Weekly, 2017)
Monogenic diabetes (MD) accounts for 1–2% of all diabetes cases. Because of its wide phenotypic spectrum, MD is often misdiagnosed as type 1 or type 2 diabetes. While clinical and biochemical parameters can suggest MD, a definitive diagnosis requires genetic analysis. We conducted a survey among clinicians specialising in diabetes to document the cases with MD. Of 74 clinically suspected MD patients, 46% had undergone genetic analysis, which was mostly conducted using Sanger’s classical sequencing method. The most common recorded mutations were located in the GCK gene, followed by the mitochondrial genome (m.3243A>G mutation) and the HNF1B and HNF1A genes. The remaining 54% of patients only had a clinical diagnosis, mostly because genetic analysis was not easily accessible. Here, we designed a new diagnostic panel of 42 genes that was developed based on the survey. The panel was validated with an independent sample of nine known MD patients. Our survey confirms the need for a comprehensive analytical instrument for the diagnosis of MD, which will be met by the proposed panel. The diagnosis of MD is crucial because it dictates treatment and may improve metabolic control and reduce long-term complications as proposed by precision medicine.